The Impacts of Perceived Social Loafing on Team Performance among Postgraduate Students in Business Program in UK - Wei, Yang (2020)
With the increasing popularity of teamwork in different organizations, especially in the higher education sector, despite the benefits teamwork brings, some problems also arise during teamwork cooperation, which largely influences team performance. One of the common problems existing in teamwork is social loafing, which means some team members unfairly take advantage of the team’s strengths while contributing less to the whole teamwork. Under this condition, this research focused on the presentation teamwork of the postgraduates studying in a business program in the UK and aimed to examine how the perceived social loafing of these postgraduates influences their team performance from their teamwork environment, teamwork process, and teamwork assessment. With this objective, this research used a qualitative approach to conduct and used semi-structured interviews to collect data. By using a proper purposive sampling strategy, 12 suitable participants were selected from different business programs and universities in the UK. After nearly 30 minutes online interview of each participant, a logic thematic analysis of the data was finally showing. In general, this research found that perceived social loafing negatively influences team performance in varying degrees from the perspective of justice perception, moods and emotions, motivation, team objective, communication, team cohesiveness, teamwork satisfaction, and efficiency. Overall, this study truly made its contribution to the understanding of the perceived social loafing, the consequences of perceived social loafing, and most importantly, it gave detailed explanations of how these consequences influence the team performance.